PENGEMBANGAN VIDEO PEMBELAJARAN PENDAMPING GAMES EDUKATIF WORDWALL UNTUK MATERI PAI SEKOLAH DASAR - Ani Nur Aeni; Dadan Djuanda; Maulana Maulana; Rini Nursaadah; Salsabila Baliani Putri Sopian (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
This research is focused on PAI material and the target of this research is elementary school students. The research approach used is a mix method with a development design using a 4-D model formulated from Thiagarajan, Semmel and Semmel. This development model contains 4 steps, namely define, design, develop, and disseminate. Research data was obtained through interviews, questionnaires, and document analysis techniques. This research produces: 1) learning video product design made based on the results of questionnaire analysis of teacher needs for PAI SD learning media and based on PAI SD curriculum analysis by analyzing Basic Competencies. From this basis, learning video products are designed that are in accordance with the characteristics of elementary school students, 2) Products in the form of wordwall companion learning videos that last 8 minutes 44 seconds. 3) Product test results that get an assessment from users with a very good predicate, meaning that the product is very suitabel for use in PAI teaching. From the results of this research, learning videos can be further developed for other materials